If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9.1x + 23.1 = -4.2 Reorder the terms: 23.1 + 9.1x = -4.2 Solving 23.1 + 9.1x = -4.2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23.1' to each side of the equation. 23.1 + -23.1 + 9.1x = -4.2 + -23.1 Combine like terms: 23.1 + -23.1 = 0.0 0.0 + 9.1x = -4.2 + -23.1 9.1x = -4.2 + -23.1 Combine like terms: -4.2 + -23.1 = -27.3 9.1x = -27.3 Divide each side by '9.1'. x = -3 Simplifying x = -3
| (5x^5y^4)(2x^5y)= | | 21b=-19 | | 7(4x-2)=322 | | 112=4x+6(x+7) | | 5x-5=33 | | 6(6m-6)=-8(-4m+5) | | -3b-3+9b=-5b-4+11b | | x+5y=-14 | | 3x-10(x+2)=13-17x | | -6y=72 | | 7x-3x=5x+13 | | 6+2(s-5t)= | | 8-(3+7)=7-9 | | -0.25x=-3.4 | | 5(w+3)+3(3w+1)=14 | | 5x+9=-5 | | -10(x-5)=100 | | .75x+.25(10-x)=.59(10) | | 3x-3=2x-9 | | 4x-10y=100 | | 2y+6y=48 | | 3(x+17)=5 | | -120=8x | | 2-3k=10 | | 6x+4+2x=42 | | -4z-7+12z=37-12 | | 6x+6=11x-24 | | 12-x=9 | | 6x+6=-34-4x | | 24=2m | | 2x+[x+3]=24 | | 33.7-(1.5s+2.3)=3.4-(0.4-5.7s) |